Enhanced degradation of ciprofloxacin via Co-doped Bi2Fe4O9 photocatalysis under peroxydisulfate activation - Zizhen Wu; Jiawei Liu; Li Zhen; Jun Shi; Huiping Deng (Green Energy & Environment, 2025)
The synergistic degradation of contaminants in water by photocatalysis and peroxydisulfate (PDS) activation has been proven to be a promising combined advanced oxidation technology. Consequently, the development of highly efficient photocatalysts that are activated by visible light and PDS is of immense importance. Herein, different proportions of cobalt-doped Bi2Fe4O9 (BFO@Co-x) photocatalysts were effectively synthesized for elimination of ciprofloxacin (CIP). The degradation efficiency of CIP achieved by the BFO@Co/Vis/PDS system attained 84.49% (k = 0.0516 min−1) under 40 min light irradiation, outperforming the BFO@Co/Vis and PDS/Vis systems by a factor of 1.45 and 3.6, respectively. Characterization and photoelectric performance assessments revealed that the fabrication of BFO@Co-0.5 was successful, enhancing the photocatalytic degradation efficiency under the synergistic effect of PDS. Moreover, the BFO@Co/Vis/PDS system demonstrated favorable adaptability to various pH, inorganic anions, and humic acid in solution. Additionally, the degradation pathways of CIP and the toxicity of products were evaluated using LC/MS and T.E.S.T software, indicating a reduction in the toxicity of CIP degradation products. This study may provide insights into the application of photocatalyst/Vis/PDS combined systems in the field of water environmental treatment.